RELATIONSHIP OF DIABETES RELATED DISTRESS WITH PSYCHOLOGICAL DISTRESS IN TYPE 2 DIABETIC PATIENTS - Sadiq, Riffat; Batool, Ayesha (Journal of Postgraduate Medical Institute, 2017)
Objectives: To examine the predictive role of diabetes related distress (emotional burden, physician-related distress, regimen-related distress and interpersonal distress) in psychological distress among type 2 diabetic patients. Methodology: It was a correlation study conducted on type 2 diabetic patients dwelling in Faisalabad city. One hundred and twenty diabetic patients were recruited through purposive convenient sampling technique. Brief interview form, 17-items diabetes distress scale and 10-items psychological distress scale were used for data collection. Linear, multiple regression analysis and independent t-test were computed via SPSS. Results: Out of 120 participants, 60 were males and 60 were females. Age ranged from 21 to 50 years (mean 37.3 ±7.48146). Diabetes distress (p =.000) emotional burden (p =.019) and interpersonal distress (p =.000) significantly predicted psychological distress among type 2 diabetic patients. Additionally, a significant gender difference was found in respect to diabetic distress (p =.000) regimen-related distress (p =.01) and interpersonal distress (p = .025). Conclusion: Diabetes related distress in the form of emotional burden and interpersonal distress are significant predictors of psychological distress among type 2 diabetic patients. However male and female diabetic patients differ in experiencing distress associated with their disease.